WORK PRODUCTIVITY : THE ROLE OF KAIZEN CULTURE AND LEADERSHIP STYLE WITH JOB SATISFACTION AS AN INTERVENING VARIABEL IN PT. NIKOMAS GEMILANG: THE ROLE OF KAIZEN CULTURE AND LEADERSHIP STYLE WITH JOB SATISFACTION - Fuadi; Susilawati, Deti; Shavab, Firli (Management Science Research Journal, 2025)
Data from the Ministry of Manpower (Kemnaker), labor productivity figures in Indonesia from 2018 to 2022 are 82.56; 85.04; 83.48; 84.85; and 86.55 (million rupiah/labor). The higher the level of productivity of a country, the greater the profits obtained, and vice versa. The aim of this research is to determine and analyze the influence of kaizen culture, leadership style, on work productivity with job satisfaction as an intervening variable. The population in the research was all employees of the production department of PT Nikomas Gemilang, totaling 2,000 people, sampling using the Slovin formula, the sample consisted of 95 respondents. The analysis technique used is multiple linear regression and path analysis with a significance level of 5%, so the results of this research show that: 1)Kaizen culture has no effect on work productivity. 2)Leadership style has no effect on work productivity. 3)Job satisfaction influences work productivity. 4)Kaizen culture influences job satisfaction. 5)Leadership style has no effect on job satisfaction. 6)Job satisfaction can mediate the influence of work culture on productivity at PT. Nikomas Gemilang in Serang City). 7)Job satisfaction cannot mediate the influence of leadership style on work productivity at PT. Nikomas Gemilang in Serang City.